Unveiling Coastal Cliff Vulnerabilities by integrating LiDAR, UAS, and AI Technologies. Case Study: NavagioShipwreck Beach, Zakynthos (Greece) - Konsolaki, A.; Vassilakis, E; Karantanellis, S; Kotsi, E.; Lekkas, E. (4th European Regional Conference of IAEG, 2024)
Coastal cliffs are one of the cases of steep terrains naturally vulnerable to a range of erosional processes, with rockfalls emerging as one of the most prevalent and hazardous. Although predicting rockfall occurrences remains challenging due to multi-faceted triggering factors such as extreme weather events, seismic activity, erosion, and human actions, technological advancements offer promising avenues for developing more robust and effective risk assessment methodologies. Light Detection and Ranging (LiDAR), photogrammetry from Unmanned Aerial System images, and satellite imagery, coupled with the evolution of artificial intelligence, have revolutionized the field of rockfall assessment by enabling precise detection and quantification of 3D topographic changes, offering insights into rockfall dynamics.